Acceptability, feasibility, fidelity and quality implementation of the culturally adapted version of the Social Competence Promotion Program among Young Adolescents (“Mi Mejor Plan”) to prevent substance use among adolescents in Chile: a pilot randomized control study - Saray Ramirez; Natalia Ríos; Cristian A. Rojas-Barahona; Marcela Cárcamo; Alejandro Sepulveda-Pañaloza; Ricardo Araya; Jorge Gaete (BMC Public Health)
Abstract Introduction Substance use among adolescents is a public health problem. We culturally adapted The Social Competence Promotion Program for Young Adolescents (SCPP-YA) program to the school context in Chile (henceforth “Mi Mejor Plan or MMP”) and assessed the acceptability, feasibility, fidelity, and quality of the implementation among 6th graders. We also explored the efficacy of the program in improving individual protective factors and reducing risk factors and substance use. Methods Cluster randomized controlled trial conducted in Chile. The schools were randomly assigned to one of two conditions in a 1:1 ratio: 1) the "MMP" intervention group, and 2) the Control group. The program consisted of a 16-h class-based curriculum promoting social problem-solving skills delivered by a trained facilitator. Primary outcomes were acceptability, feasibility, fidelity, and quality of the implementation using detailed reports of facilitators and from observers of the performance of the facilitators in vivo. Additionally, we explored the efficacy of the intervention on secondary outcomes: 30-day prevalence of tobacco, alcohol, and cannabis use and individual risk and protective factors promoted by MMP. We performed an intention-to-treat analysis using mixed models, taking into account the hierarchical nature of the data. Results Seven hundred sixty-five 6th graders from 11 schools were enrolled (one school dropped out after the randomization); 608 were analyzed at baseline, and 538 were analyzed post-intervention. 52.5% were male, and the average age was 11.3 in both groups. All 16 sessions were implemented, and students’ attendance at each session ranged from 83.8% to 92.4%. The program was generally well-received, with up to 91.3% of students rating acceptability positively. Facilitators and observers reported high adherence to the contents of the program in most sessions. Protective factors, such as negative beliefs about tobacco and alcohol, increased significantly in the IG. Still, there were no significant changes in substance use, risk factors, emotion regulation, or school membership. Conclusions The MMP program was well accepted, and we achieved high levels of implementation and fidelity. The program improved some individual protective factors, such as negative beliefs about tobacco and alcohol, with no changes in substance use among adolescents. Trial registration ClinicalTrials.gov, number NCT04236947; registration date: 17/01/2020.